Polyvinyl Pyrrolidone/Nickel Oxide (PVP/NiO) Nanocomposite: Synthesis, Characterization, and Removal Study of Eosin Y Using Adsorption Process - َaliakbar Dehno Khalaji; Emad Jafari; Moslem Emami; egin Mohammadi (Nanochemistry Research)
In this study, the PVP/NiO nanocomposite was synthesized using the solution cast technique and characterized by Fourier transform infra-red (FT-IR), X-ray powder diffraction (XRD), thermogravimetric analysis (TGA), differential thermal analysis (DTA), energy-dispersive X-ray spectroscopy (EDS), and scanning electron microscope (SEM). The results confirmed the successful preparation of PVP/NiO. The as-prepared PVP/NiO was used as a new adsorbent for the removal of eosin Y (EY) dye from aqueous solution at room temperature. The effect of different important parameters such as solution pH, adsorbent dose, and contact time on the adsorption efficiency of EY was investigated. The maximum adsorption capacity was found to be 101.58 mg/g at the initial pH solution of 3, 0.025 g adsorbent dose, and 90 min of contact time. The kinetic study indicated that the remove of EY was followed by a pseudo second-order (PSO) model. Then, the as-prepared PVP/NiO possessed well adsorption potential for the removal of other organic dyes from aqueous solution.